2020
DOI: 10.3389/fendo.2019.00906
|View full text |Cite
|
Sign up to set email alerts
|

Hypogonadism and Cryptorchidism

Abstract: Congenital cryptorchidism (undescended testis) is one of the most common congenital urogenital malformations in boys. Prevalence of cryptorchidism at birth among boys born with normal birth weight ranges from 1.8 to 8.4%. Cryptorchidism is associated with a risk of low semen quality and an increased risk of testicular germ cell tumors. Testicular hormones, androgens and insulin-like peptide 3 (INSL3), have an essential role in the process of testicular descent from intra-abdominal position into the scrotum in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 247 publications
(326 reference statements)
1
83
0
4
Order By: Relevance
“…(2) Congenital cryptorchidism (undescended testis) is one of the most common congenital urogenital malformations in children and was recently reviewed by Rodprasert et al [140], who reported that the prevalence at birth among children born with normal weight ranges between 1.8% and 8.4%. This condition is associated with a future risk of poor semen quality and an increased risk of developing testicular germ cell tumors and is related to the RXFP2 gene (13q13.1), but as already mentioned, androgens and INSL3 (at 19p13.11) also play a role in the process of testicular descent.…”
Section: Male Ps or Mad Due To Defects In Androgenic Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) Congenital cryptorchidism (undescended testis) is one of the most common congenital urogenital malformations in children and was recently reviewed by Rodprasert et al [140], who reported that the prevalence at birth among children born with normal weight ranges between 1.8% and 8.4%. This condition is associated with a future risk of poor semen quality and an increased risk of developing testicular germ cell tumors and is related to the RXFP2 gene (13q13.1), but as already mentioned, androgens and INSL3 (at 19p13.11) also play a role in the process of testicular descent.…”
Section: Male Ps or Mad Due To Defects In Androgenic Actionmentioning
confidence: 99%
“…However, evidence regarding the benefits of early orchidopexy for testicular endocrine function is controversial, and also hormonal treatments that use hCG or Gonadotropin-Releasing Hormone (GnRH) to induce testicular descent have low success rates. More research is needed to evaluate the effects of hormonal treatments on future male reproductive health [140].…”
Section: Male Ps or Mad Due To Defects In Androgenic Actionmentioning
confidence: 99%
“…AMH secretion from the fetal Sertoli cells causes regression of the müllerian or paramesonephric ducts and prevents the formation of a uterus and fallopian tubes ( 2 ). Testicular descent is a complex process involving genetic, anatomical, hormonal and environmental factors and conditions affecting any of this factors can cause cryptorchidism ( 3 ). Previous authors have described cases of cryptorchidism associated with CF ( 4 ); Differentiating between cryptorchidism and testicular atrophy is a diagnostic challenge.…”
Section: Discussionmentioning
confidence: 99%
“…AGD is considered a marker of endocrine disruption and reproductive disease [63,64]. Tang and colleagues found LC-PCBs to be associated with lower levels of luteinizing hormone and testosterone [58], which are crucial hormones in the process of testicular descent in fetal life [65].…”
Section: Previous Literature and Mechanismsmentioning
confidence: 99%